A Note on the Maximal Functions on Weighted Harmonic AN Groups - Wu, Yurong; Zhao, Shiliang (Chinese annals of mathematics. Serie B, 2016)
In this paper, the authors point out that the methods used by Li（2004, 2005,2007） can be applied to study maximal functions on weighted harmonic AN groups.